2024
DOI: 10.3390/coatings14030275
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Azopolymer for Photo-Switchable Adhesive Applications

David Siniscalco,
Laurence Pessoni,
Anne Boussonnière
et al.

Abstract: Significant research endeavors have been devoted to developing adhesives with reversible switching capabilities, allowing them to activate adhesion in response to diverse environmental stimuli. Among these, photo-switchable adhesives stand out as particularly promising. The presence of a photo-reversible solid-to-liquid transition, characterized by a transition temperature (TSL), in certain azobenzene-containing polymers offers a compelling avenue for creating such adhesives. The development of a method based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…When the stimulus responsible for the change returns to its initial state, the changed physicochemical properties return to their initial state. pH, temperature, light, and magnetic field are among the most common stimuli in the literature [4][5][6][7]. Considering the role of solvents in chemical and biochemical processes, it can be suggested that pH is a highly effective stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…When the stimulus responsible for the change returns to its initial state, the changed physicochemical properties return to their initial state. pH, temperature, light, and magnetic field are among the most common stimuli in the literature [4][5][6][7]. Considering the role of solvents in chemical and biochemical processes, it can be suggested that pH is a highly effective stimulus.…”
Section: Introductionmentioning
confidence: 99%